Fibula Osteocutaneous flap for mandible reconstruction after ameloblastoma resection: amending technique to reduce ischaemic time - Chee, E.K.; Ahmad, T.S.; Ng, E.S. (Malaysian Orthopaedic Association, 2007)
A 27-year-old patient with ameloblastoma of the mandible underwent anterior mandibulectomy and reconstruction with left fibula osteocutaneous flap. The bone was shaped at the lower limb before cutting the pedicle. Vascularised free fibula flap provides a good alternative to other bone grafts in mandible reconstruction as it is relatively easy to perform, carries a low complication rate, and mandibular shaping with intact pedicle cuts down on ischaemic as well as total operative time.